Antecedents and references within the context of Arts-based research (Islas, 2024)
Introduction: Defining and declaring the antecedents and references involved in the process of creating a work of Visual Arts is crucial for developing a proposal grounded in both production and the underlying visual theory. Misunderstanding these terms complicates the conceptualization and operational processes, especially in qualitative research and those assuming artistic creation as a result. This article addresses a specificity of practice-based arts research, focusing on the contextualization of the study's theme, with the objective to identify, define, and describe antecedents and references while highlighting new elements that can enhance their utilization.Methods: Employing action research, the study utilizes participant observation and document analysis, establishing a reference point within the context of practice-based arts research.Results: The article identifies and analyzes considerations essential for understanding these terms within the realm of Visual Theory, specifying each one and highlighting new elements that can enrich their definition and application.Conclusions: Experiences related to the research-creation processes of a work of Visual Arts are crucial for defining and declaring the antecedents and references in practice-based arts research. Systematizing experiential and professional insights into these practices in Cuba facilitates the achievement and realization of artistic results applicable to any qualitative research and those involving the creation of artistic phenomena.
Keywords: Arts-based research; antecedents; references; Visual Arts